The reporting of research ethics committee approval and informed consent in otolaryngology journals. (February 2015) - Murphy, S.; Nolan, C.; O'Rourke, C.; Fenton, J.E.
<x xml:space="preserve">Abstract</x> Objectives Medical research involving human subjects must follow ethical standards as outlined in the Declaration of Helsinki of the World Medical Association. The aim of this study was to assess the frequency of reporting of informed consent and regional ethical committee (REC) approval in all reports of trials published in the major European Otolaryngology journals. Design Review of all clinical research articles published online in the calendar year 2012. Setting Three leading European Otolaryngology journals. Participants Clinical Otolaryngology, The Journal of Laryngology and Otology and The European Achieves of Oto‐Rhino‐Laryngology. Main outcome measures Evaluate the incidence of reporting of REC approval and informed consent. Results Of the 767 articles reviewed, 401 met the inclusion criteria (manuscripts reporting human subjects, human tissue or identifiable personal data research which require ethical approval). 49.9% lacked a statement of REC approval and 42.9% lacked disclosure of informed consent. Articles that did not state REC approval were associated with not stating informed consent (P < 0.05). Conclusion Articles that lack explicit statements of REC approval and informed consent are frequent and continue to be published in major otolaryngology journals.